Effect of PZN addition on piezoelectric and ferroelectric properties of Pb(Zr1/2Ti1/2)O3 ceramics - Tanabat Promjun (2018)
Ceramics in the xPb(Zn 1/3 Nb 2/3 )O 3 -(1-x)Pb(Zr 1/2 Ti 1/2 )O 3 [xPZN-(1-x)PZT] solid solution system are expected to display excellent dielectric, piezoelectric, and ferroelectric properties in compositions close to the morphotropic phase boundary (MPB). The dielectric behavior of ceramics with x = 0.1 - 0.5 has been characterized in order to identify the MPB compositions in this system. Combined with x-ray diffraction analysis, dielectric, piezoelectric and ferroelectric measurements, it was consistently shown that an MPB exists around x = 0.3 in this binary system. When x £ 0.2, the tetragonal phase dominates at ambient temperatures. In the range of x 3 0.4, the rhombohedral phase dominates. © (2014) Trans Tech Publications, Switzerland.